Personalisasi Pendidikan Berbasis AI dalam Meningkatkan Kualitas Belajar Siswa - Yanto, Masti; Mad Sa’I; Nailatur Rizqiyah (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
The development of artificial intelligence (AI) technology has opened up new opportunities in education, one of which is through the implementation of personalized learning. This study aims to investigate the impact of using AI in personalizing education on improving the quality of student learning in schools. The research method used a qualitative approach with a descriptive design. The results show that the application of AI in personalized learning can significantly improve student learning outcomes, with an average increase of 15% compared to conventional methods. In addition, students’ learning motivation also increased by 20%, as learning becomes more relevant, interactive, and tailored to individual needs. However, this study also found some challenges, such as gaps in technology access, data privacy concerns, and the need for training for teachers to maximize the potential of AI. Overall, this research shows that personalization-based AI has great potential to revolutionize the education system by creating a more inclusive and effective learning environment. The implications of this research can be used as a basis for the development of future technology-oriented education policies.